A Review of the Evaluation, Control, and Application Technologies for Drill String Vibrations and Shocks in Oil and Gas Well. (20th October 2016) - Dong, Guangjian; Chen, Ping
Abstract : Drill string vibrations and shocks (V&S) can limit the optimization of drilling performance, which is a key problem for trajectory optimizing, wellbore design, increasing drill tools life, rate of penetration, and intelligent drilling. The directional wells and other special trajectory drilling technologies are often used in deep water, deep well, hard rock, and brittle shale formations. In drilling these complex wells, the cost caused by V&S increases. According to past theories, indoor experiments, and field studies, the relations among ten kinds of V&S, which contain basic forms, response frequency, and amplitude, are summarized and discussed. Two evaluation methods are compared systematically, such as theoretical and measurement methods. Typical vibration measurement tools are investigated and discussed. The control technologies for drill string V&S are divided into passive control, active control, and semiactive control. Key methods for and critical equipment of three control types are compared. Based on the past development, a controlling program of drill string V&S is devised. Application technologies of the drill string V&S are discussed, such as improving the rate of penetration, controlling borehole trajectory, finding source of seismic while drilling, and reducing the friction of drill string. Related discussions and recommendations for evaluating, controlling, and applying the drill string V&S are made.